Who wants to work in a rural health post? The role of intrinsic motivation, rural background and faith-based institutions in Rwanda and Ethiopia - Pieter Serneels; Jose G. Montalvo; Gunilla Pettersson; Tomas Lievens; Jean Damascene Butera; Aklilu Kidanu (Institute for the Study of Labor (IZA), 2010)
Most developing countries face shortages of health workers in rural areas. This has profound consequences for health service delivery, and ultimately for health outcomes. To design policies that rectify these geographic imbalances it is vital to understand what factors determine health workers' choice to work in rural areas. But empirical analysis of health worker preferences has remained limited due to the lack of data. Using unique contingent valuation data from a cohort survey of 412 nursing and medical students in Rwanda, this paper examines the determinants of future health workers' willingness to work in rural areas, as measured by rural reservation wages, using regression analysis. These data are also combined with those from an identical survey in Ethiopia to enable a two-country analysis. We find that health workers with higher intrinsic motivation - measured as the importance attached to helping the poor - as well as those who have grown up in a rural area, and Adventists who participate in a local bonding scheme are all significantly more willing to work in a rural area. The main Rwanda result for intrinsic motivation is strikingly similar to that obtained for Ethiopia and Rwanda together. These results suggest that in addition to economic incentives, intrinsic motivation and rural origin play an important role in health workers' decisions to work in a rural area, and that faith-based institutions matter.
Keywords: J22; I11; 330; Health care delivery; health workers; labour supply; public service; Gesundheitsberufe; Motivation; Ländlicher Raum; Gesundheitswesen; Äthiopien; Ruanda